Math Problem Statement

consider (𝑞𝑞 → 𝑝𝑝) ∧ ~(𝑟𝑟 ∧ 𝑞𝑞), Simplify this statement, explaining all your steps (make sure to use the correct names of the logical equivalences)

Solution

We are tasked with simplifying the logical statement (qp)¬(rq)(q \rightarrow p) \land \neg(r \land q).

Step 1: Use Implication Law

The implication qpq \rightarrow p can be rewritten using the Implication Law: qp¬qpq \rightarrow p \equiv \neg q \lor p So, the original expression becomes: (¬qp)¬(rq)(\neg q \lor p) \land \neg(r \land q)

Step 2: Apply De Morgan's Law to Negation

Next, let's simplify ¬(rq)\neg(r \land q) using De Morgan's Law. This law states that: ¬(rq)¬r¬q\neg(r \land q) \equiv \neg r \lor \neg q So, the expression becomes: (¬qp)(¬r¬q)(\neg q \lor p) \land (\neg r \lor \neg q)

Step 3: Apply the Distributive Law

Now, distribute (¬qp)(\neg q \lor p) over (¬r¬q)(\neg r \lor \neg q) using the Distributive Law: (¬qp)(¬r¬q)(¬q(¬r¬q))(p(¬r¬q))(\neg q \lor p) \land (\neg r \lor \neg q) \equiv (\neg q \land (\neg r \lor \neg q)) \lor (p \land (\neg r \lor \neg q)) Simplify the two parts of the expression:

  1. ¬q(¬r¬q)\neg q \land (\neg r \lor \neg q): Since ¬q\neg q appears in both terms, we simplify this part to just ¬q\neg q (by Idempotent Law).

  2. p(¬r¬q)p \land (\neg r \lor \neg q): Distribute pp over ¬r¬q\neg r \lor \neg q: p(¬r¬q)(p¬r)(p¬q)p \land (\neg r \lor \neg q) \equiv (p \land \neg r) \lor (p \land \neg q)

Step 4: Combine the Results

Now we combine the results from the two parts: ¬q((p¬r)(p¬q))\neg q \lor ((p \land \neg r) \lor (p \land \neg q)) We can simplify this further using the Associative Law and Distributive Law: ¬q(p¬r)(p¬q)\neg q \lor (p \land \neg r) \lor (p \land \neg q)

Final Simplified Expression

Thus, the simplified form of the original expression is: ¬q(p¬r)(p¬q)\neg q \lor (p \land \neg r) \lor (p \land \neg q)

Recap of Steps:

  1. Applied Implication Law: qp¬qpq \rightarrow p \equiv \neg q \lor p.
  2. Applied De Morgan's Law: ¬(rq)¬r¬q\neg(r \land q) \equiv \neg r \lor \neg q.
  3. Applied Distributive Law to distribute ¬qp\neg q \lor p over ¬r¬q\neg r \lor \neg q.
  4. Simplified the result using the Idempotent Law and Associative Law.

Do you want more details on any of these steps or the logical laws?

Here are five related questions for further exploration:

  1. How would you simplify (pq)¬(pr)(p \lor q) \land \neg(p \land r)?
  2. What is the negation of (qp)r(q \rightarrow p) \land r?
  3. Can you simplify p(qr)p \rightarrow (q \rightarrow r) using logical equivalences?
  4. How do De Morgan's Laws apply to three terms, e.g., ¬(pqr)\neg(p \land q \land r)?
  5. What is the equivalent disjunctive normal form (DNF) of the simplified expression?

Tip: Always apply De Morgan’s laws when dealing with negations over conjunctions or disjunctions.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Propositional Logic
Logical Equivalences

Formulas

Implication Law: q → p ≡ ¬q ∨ p
De Morgan's Law: ¬(r ∧ q) ≡ ¬r ∨ ¬q
Distributive Law: (A ∨ B) ∧ (C ∨ D) ≡ (A ∧ C) ∨ (A ∧ D) ∨ (B ∧ C) ∨ (B ∧ D)
Idempotent Law: A ∧ A ≡ A
Associative Law: A ∨ (B ∨ C) ≡ (A ∨ B) ∨ C

Theorems

Implication Law
De Morgan's Law
Distributive Law
Idempotent Law
Associative Law

Suitable Grade Level

Grades 10-12